Prevalence of chlamydophila psittaci infection in pigeons and paraquets by a real time polymerase chain reaction - Nevin Tuzcu; Hasan Huseyin Hadimli; Aysegul Ilban (Eurasian Journal of Veterinary Sciences)
Aim: Avian chlamydiosis is a systemic, zoonotic, sometimes fatal disease caused by Chlamydophila psittaci in domestic and wild poultry. Although C. psittaci does not always cause serious disease in poultry, it can cause serious disease especially in immunosuppressive humans. The aim of this study was to determine the prevalence of C. psittaci, in stool samples of pigeons and paraquets, in Konya province. Materials and Methods: Fifty pigeon feces samples taken from a total of 600 pigeons belonging to 24 different breeders and 52 fecal samples taken from 632 paraquets from 30 different breeders were the samples in this study. The presence of C. psittaci was investigated by Real Time PCR based on the presence of ompA gene in these samples. Results: The presence of C.psittaci ompA gene was determined as 2% and 1%, respectively, by real time PCR in stool samples of pigeons and paraquet in Konya region. Conclusion: The fact that the disease is zoonotic and people's close contact with poultry, especially pigeons and caged birds is increased the importance of the disease in terms of public healthday day by day.